Examining the contribution of fiscal policy on economic growth: Analytical insights from Pakistan - Hassan, Muhammad Iatzaz Ul; WU, Mengyun; Awan, Muhammad Bilal; Anjum, Hafiz Naveed; Akhtar, Sadaf (International Journal of Emerging Trends in Social Sciences, 2023)
To better understand the influence of fiscal policy (FP) on economic growth (EG) in Pakistan, this study investigates the importance of the amount of output produced by different factors of production in Pakistan's economy. The annual time series data has been collected from the State Bank of Pakistan and World Bank Data-Base from the years (2001-2020). The Autoregressive Distributed Lag (ARDL) model is used for empirical research to assess the significant factors of EG, and the Augmented Dickey-Fuller (ADF) unit root test is used to ensure that all of the variables are stationary. Using annual time series data from 2001 to 2020. Based on these findings, this study recommends adopting a proactive fiscal policy framework that incorporates expansionary measures. We argue that this strategy has the capacity to stimulate and maintain Pakistan's economic growth path, thereby fostering a more promising and prosperous future. Moreover, the study found the impact of government expenditures (GE), gross fixed capital creation (GFCC), and direct and indirect taxes on Gross domestic Product (GDP). Additionally, findings showed that government expenditures, gross fixed capital creation, indirect, and direct taxes have a strong effect on economic growth. It is argued that an expansionary fiscal policy in the future could greatly benefit Pakistan's economic growth.